Nasal Chondromesenchymal Hamartoma with Skull Base and Orbital Involvement: Case Presentation - Golbin, Denis A (Cureus, 2018)
Nasal chondromesenchymal hamartoma (NCMH) is a rare benign tumor of the sinonasal tract in children with possible orbit and skull base involvement. We present the 57th published observation of this kind of tumor. A 25-month-old female patient presented with recurrent mass lesion of the sinonasal tract. According to her history, she had feeding difficulties and nasal obstruction since birth. She underwent partial resection at eight months of age via transfacial approach in the local hospital. Due to progression of tumor remnants, a second surgery was performed using an endoscopic endonasal approach resulting in subtotal resection. At 12 months of follow-up, a good postoperative result was observed with no signs of tumor progression despite incomplete resection. Histological and immunohistochemical examination of the biopsy specimens is presented. Comparison of specimens obtained from each of the two surgeries showed a difference in histological patterns. Endoscopic endonasal approach is the mainstay of surgical management. In case of incomplete resection, careful follow-up MRI studies should be recommended.